PENGABDIAN MASYARAKAT KEPADA PEMUDA AWAL MENGENAI DAMPAK GADGET Di SMK St.NAHANSON PARAPAT SIPOHOLON - July Trisnawati Hutabarat; Kristina Ompusunggu; Leni Elisa Silaban; Lasrin Aliando Padang; Damayanti Nababan (Perigel: Jurnal Penyuluhan Masyarakat Indonesia, 2022)
Abstract Gadget is a small device that has a special function related to today's technological developments. Almost all humans, especially high school/vocational school children nowadays, already have Gadgets. Gadgets are used to meet the needs of today's life which is the main target in everyday life. The impact of using positive gadgets is as a good learning tool, but the negative impact of gadgets makes attitudes that are not good or affect one's behavior and health. So from that, the author provides community service to early youth regarding the impact of Gadgets at St. Vocational High School. Nahanson parapat sipoholon, to use Gadgets in a good way. The method used by the author is the Qualitative Method, in which the author gives an explanation through material regarding the impact of gadgets. the development of globalization with the demands of the need for rapid exchange of information, the role of technology has become very important. So that it makes users uncontrollable in using these gadget